2014
DOI: 10.1136/neurintsurg-2014-011343.22
|View full text |Cite
|
Sign up to set email alerts
|

O-022 A New Protocol for Anticoagulation with Tirofiban during Stenting of Intracranial Aneurysms

Abstract: Introduction Stenting techniques such as stent-assisted coiling and flow diversion are increasingly used for treatment of intracranial aneurysms. In previous reports, patients were pretreated were aspirin and clopidogrel prior to the intervention for prevention of thromboembolic complications. Prior studies also often rely on aspirin response and P2Y assessment, which often delays treatment in non-responders. The present study assesses the safety and efficacy of a new protocol for anticoagulation using tirofib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Later, several studies suggested a protocol of 0.1-g/kg/min maintenance infusion without a loading dose for stent placement of intracranial aneurysms. 20,32 The pharmaceutical company Merck & Co. recommended that the infusion should be continued through angiography and for 12-24 hours after angioplasty or atherectomy. 33 Tirofiban infusion was, therefore, continued for 12-24 hours after the procedure in our study.…”
Section: -12mentioning
confidence: 99%
“…Later, several studies suggested a protocol of 0.1-g/kg/min maintenance infusion without a loading dose for stent placement of intracranial aneurysms. 20,32 The pharmaceutical company Merck & Co. recommended that the infusion should be continued through angiography and for 12-24 hours after angioplasty or atherectomy. 33 Tirofiban infusion was, therefore, continued for 12-24 hours after the procedure in our study.…”
Section: -12mentioning
confidence: 99%